QUALITATIVE CHARACTERISTICS AS A RELIABLE TOOL FOR ASSESSING THE QUALITY OF ACCOUNTING INFORMATION: AN OVERVIEW STUDY - Alasbahi, Aiman Hamood Mohammed Ali; P, Ishwara (International Journal of Research -GRANTHAALAYAH, 2021)
The accounting information contained in the financial reports is considered to be of a quality if it possesses a set of characteristics. Professional organizations have been concerned with the issuance of standards and the determination of characteristics related to the quality of accounting information. This paper aims to clarify the dependability on the qualitative characteristics of accounting information as an indicator of the quality of accounting information. The historical approach is used for the purpose of this study. The paper revealed that the qualitative characteristics of accounting information are a dependable indicator of the quality of accounting information and useful for decision-making